Utilization of Artificial Natural Gas Technology to Address LPG Scarcity in MSMEs: Pemanfaatan Teknologi Gas Alam Buatan untuk Mengatasi Kelangkaan LPG pada UMKM - Ninda Lutfiani; Ersa Aura Natasya; Nuryani Nuryani; Sri Watini; Muttaqin Choiri; Sigit Anggoro (ADI Pengabdian Kepada Masyarakat, 2025)
The scarcity of LPG gas that often occurs in urban areas has become a serious challenge for Micro, Small, and Medium Enterprises (MSMEs). This condition causes an increase in operational costs and creates uncertainty in energy supply, thus directly impacting business continuity. This community service aims to}overcome these problems by introducing artificial natural gas technology as a sustainable alternative solution. The main problem raised is the high dependence of MSMEs on LPG gas, while its availability is increasingly limited amid increasing demand. The methods used in this community service activity include observation of the energy needs of MSME actors, application of biogas technology to produce artificial natural gas, and technical training on how to operate and maintain the system. Activities are carried out through a participatory approach to ensure understanding and active involvement of the target community. The results of the community service show that the use of artificial natural gas can significantly reduce dependence on LPG, reduce energy costs, and increase the sustainability and operational efficiency of MSMEs. The conclusion of this service is that the application of artificial natural gas technology not only helps overcome the scarcity of LPG, but also makes a real contribution to achieving the Sustainable Development Goals (SDGs), especially goals 7 (Affordable and Clean Energy), 8 (Decent Work and Economic Growth), and 13 (Addressing Climate Change).